Use of agrobiodiversity and crop management practices for climate change adaptation in high hill agriculture of Nepal - Ghimire, Yuga N.; Rana, Ram B.; Ale, Shanti; Poudel, Indra; Tamang, Bir B. (Journal of Agriculture and Environment, 2018)
This paper highlights the effects of climate related hazards in crops and the existing adaptation practices in the high hills of Nepal. First, interaction meeting held in Kathmandu decided to select three districts: Humla, Kaski and Solukhumbhu as the representative districts. Second, stakeholder interaction meetings held in respective districts selected three villages: Chhipra from Humla district, Lumle from Kaski district and Takashindu from Solukhumbhu district. Information was acquired using Focus Group Discussion with the use of diversity analysis tools viz. four-cell analysis, noting traits of local crop genetic resources, and matrix ranking of crop varieties. The study found that climate hazards were increasing in recent years affecting farming adversely. Existing adaptation practices included change of crops and cropping pattern and use of alternate crop management strategies. Tourism, low social value attached to traditional crops, inadequate research, and food subsidy and other forms of external support have been identified as the threat to agrobiodiversity conservation in high hills of Nepal. Promotion of agro-tourism, identifying crop varieties tolerant to extreme weather events and their promotion through technology development and value addition have been suggested to combat climate change effects in high hill agriculture in the country.